A landscape assessment of the use of patient reported outcome measures in research, quality improvement and clinical care across a healthcare organisation - David A. Snowdon; Velandai Srikanth; Richard Beare; Lucy Marsh; Emily Parker; Kim Naude; Nadine E. Andrew (BMC Health Services Research, 2023)
Abstract Background Patient reported outcome measures (PROMs) can be used by healthcare organisations to inform improvements in service delivery. However, routine collection of PROMs is difficult to achieve across an entire healthcare organisation. An understanding of the use of PROMs within an organisation can provide valuable insights on the purpose, scope and practical considerations of PROMs collection, which can inform implementation of PROMs. Methods We used multiple research methods to assess the use of PROMs in research projects, data registries and clinical care across a healthcare organisation from January 2014 to April 2021. The methods included an audit of ethics applications approved by the organisation’s human research ethics committee and registries which the health organisation had contributed data to; a literature review of peer-reviewed journal articles reporting on research projects conducted at the organisation; and a survey of health professionals use of PROMs in research projects, data registries and clinical care. The scope of PROMs was determined by classifying PROMs as either ‘specific’ to a particular disease and/or condition, or as a ‘generic’ measure with further classification based on the health domains they measured, using the World Health Organization International Classification Framework. Practical considerations included mode and timing of PROMs administration. Data were described using frequency and proportion. Results PROMs were used by 22% of research projects (n = 144/666), 68% of data registries (n = 13/19), and 76% of clinical specialties in their clinical care (n = 16/21). Disease specific PROMs were most commonly used: 83% of research projects (n = 130/144), 69% of clinical registries (n = 9/13), and 75% of clinical specialties (n = 12/16). Greater than 80% of research projects, clinical registries and clinical specialties measured health domains relating to both body impairments and participation in daily life activities. The most commonly used generic PROM was the EQ-5D (research projects n = 56/144, 39%; data registries n = 5/13, 38%; clinical specialties n = 4/16, 25%). PROMs used in clinical care were mostly paper-based (n = 47/55, 85%). Conclusions We have elicited information on the use of PROMs to inform a health organisation wide implementation strategy. Future work will determine clinician and patient acceptability of the EQ-5D, and co-design a system for the collection of PROMs.